(untitled) (Jurnal Teknodik, 2019)
School headmasters in the globalization era play important roles to improve the quality of education in schools. They are educators, managers, administrators, supervisors, leaders, innovators, and motivators. Because of their important roles, they must have six competences, that are to develop, communicate and apply their schools’ vision; to create conducive educational environment; to use their schools’ resources to create conducive educational environment; to work together with students’ parents and society; to be good role models; and to affect wider social and political environment. The competences must be able to measure and may support effective leadership